Fatores Determinantes da ocupação costeira nas praias da Costa Brava, Balneário de Camboriú (SC) - ESTEVES, LUCIANA SLOMP (Pesquisas em Geociências, 2001)
Balneário Camboriú is located in the Central-North coast of the Santa Catarina state, southern Brazil. Tourism plays an important role in local and state economies. Although permanent population of Balneário Camboriú is about 70,000 inhabitants, about 1.000,000 people visit the city from December to February. The central beach is the most popular, while further south are the less intensely used beaches of the Costa Brava, Taquarinhas, Taquaras, Pinho, Estaleiro and Estaleirinho. These beaches have received few visitors, mainly due to difficulties in access. However, a scenic paved route (Interpraias) linking the beaches of Costa Brava to the central beach was recently concluded. As transport infrastructure is a main factor for the development of tourist areas, it is expected that the nearly preserved state of the Costa Brava shorelines will change fast in the near future. Thus, it is important to determine the present conditions of these beaches to monitor the imminent impacts and evaluate additional characteristics that might influence occupation in the near future. Taquaras and Pinho are special cases as the first one is still undeveloped with no car access and the second is a private beach open only for naturists. In February 21, 2001, 25% of Taquaras beachfront length was urbanized, while Estaleiro and Estaleirinho had 47% and 43% of urbanized shorelines, respectively. Urbanization usually occur at the dunes place, so dune vegetation was preserved along 72%, 27%, and 35% of the Taquaras, Estaleiro and Estaleirinho beach lengths, respectively. The morphodynamic characteristics of the Costa Brava beaches might act against tourism development although their state of natural preservation is a factor that already attracts visitors. Maintenance of the natural scenery and regulation of future occupation are the keys to tourism development at Costa Brava beaches.